Understanding the volatile flavour changes during accelerated shelf-life testing of oats using chemometrics and kinetic modelling. (30th March 2023) - Li, Xingchen; Oey, Indrawati; Leong, Sze Ying; Kebede, Biniam
Graphical abstract: Highlight: The formation of volatiles significantly increased due to storage time. Potential accelerated shelf-life testing volatile markers were selected. Lipid oxidation and Maillard reaction enhanced the volatile formation. An empirical logistic model adequately modelled the volatile formation. Abstract: This study investigated volatile flavour changes during accelerated shelf-life testing (ASLT) of oats using chemometrics and kinetic modelling. Oat samples were stored at 15, 25, 35 and 45 °C for up to 42 weeks. Headspace fingerprinting enabled the detection of a wide range of volatiles. Chemometrics was applied to explore the volatile changes and related reaction pathways and identify discriminant compounds. Most volatiles significantly increased as a function of time and could be linked to lipid oxidation and the Maillard reaction. Volatiles, such as hexanal, could be selected as potential ASLT markers for processed oat products. The volatile changes were adequately modelled using an empirical logistic model to estimate reaction rate constant and temperature dependency. Based on the estimated kinetic parameters, the selective ASLT markers could be used as a reference to track volatile changes, control off-flavour generation and improve oat product storage stability.